Evaluasi Implementasi Pendidikan Karakter di SD Negeri 5 Betung Kabupaten Banyuasin - Maryati, Maryati; Lian, Bukman; Sari, Artanti Puspita (Journal of Innovation in Teaching and Instructional Media, 2020)
This study aims to describe the achievements of character education programs in the implementation of learning activities, extracurricular activities, and the application of character education civilization programs at Elementary School 5 Betung Regency of Banyuasin. This study uses the CIPP model (Context, Input, Process, and Product) as a to for evaluating. The method used is this study is descriptive. Data collection in the evaluation process is interview, observation, and document study. The data analysis technique used in this study is data reduction, data presentation, and conclusion drawing. Sources of data were obtained from headmaster, homerooms, teachers, 5th of A grade students, and 10 representatives student guardians from grade 5.A. The results of the study show that character education programs have achieved very good results carried out by school residents. At the context stage the average achievement in the very good category, at the input stage in the very good category, at the process stage in the very good category, and at the product stage in the good category.